2014
DOI: 10.1155/2014/987272
|View full text |Cite
|
Sign up to set email alerts
|

An Interesting Cause of Hyperandrogenemic Hirsutism

Abstract: Mild clinical signs of hyperandrogenism such as hirsutism may appear during the menopausal transition as part of the normal aging process, but the development of frank virilization suggests a specific source of androgen excess. We report a case of a 68-year-old woman with signs of virilization that had started 6 months before. Clinical analyses revealed high levels of serum testosterone for a postmenopausal woman. Pelvic MRI and abdomen CT showed no evidence of ovarian and adrenal tumor. Postmenopausal hyperan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Hirsutism can be found in approximately 50% of patients with CS mainly attributed to adrenal androgen excess; endogenous hypercortisolism also correlates positively with free androgen levels probably due to SHBG reduction [2,6]. In our case, there was no adrenal mass in the adrenal CT, serum cortisol was normally suppressed after a 1-mg overnight dexamethasone suppression test and urinary free cortisol levels were into a normal range, excluding the possibility of hypercortisolism.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Hirsutism can be found in approximately 50% of patients with CS mainly attributed to adrenal androgen excess; endogenous hypercortisolism also correlates positively with free androgen levels probably due to SHBG reduction [2,6]. In our case, there was no adrenal mass in the adrenal CT, serum cortisol was normally suppressed after a 1-mg overnight dexamethasone suppression test and urinary free cortisol levels were into a normal range, excluding the possibility of hypercortisolism.…”
Section: Discussionmentioning
confidence: 56%
“…Drugs most commonly responsible include androgens, anabolic steroids, and antiepileptics [6]. A study on the effect of levetiracetam (LEV) on steroidogenesis in forskolin-stimulated H295R cells showed that LEV exposure apparently had a minimal effect on hormone secretion that could be considered as biologically significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical manifestations of hyperandrogenism include hirsutism, alopecia, acne, virilization, and emotional distress [1]. Common causes of hyperandrogenism are polycystic ovary syndrome (PCOS), congenital adrenal hyperplasia (CAH), Cushing's syndrome, and ovarian tumors [2]. At reproductive age, PCOS is considered the most frequent cause of high androgens in females [2].…”
Section: Introductionmentioning
confidence: 99%